The Legal Liability of a Notary for the Criminal Act of Forging an Authentic Deed They Created (Judge's Verdict Number 248/Pid.B/2022/PN.Jkt.Bar) - Dhania Ekky Onny Rahmawati (Green Publisher Indonesia, 2025)
Forgery of an authentic deed refers to the act of making or altering an authentic deed in an unauthorized or incorrect manner. An authentic deed is a deed made by a Notary or other public official that has perfect evidentiary power. Forgery of an authentic deed can involve various actions, such as making a false deed, changing the actual contents of the deed, or making a deed with false information. In the legal context, Notaries involved in the forgery of authentic deeds can be charged with Article 264 paragraph (1) to 1 of the Criminal Code, with a maximum imprisonment of 8 years. The formulation of the problem of Notary's Legal Responsibility for the Criminal Act of Forgery of Authentic Deed Made in Judge's Decision Number 248/Pid.B/2022/Pn.Jkt Bar and Legal Consequences Arising from the Criminal Act of Forgery of Authentic Deed by Notary. This research uses a normative juridical research method with a statutory approach, a case approach and a conceptual approach. The results of the study are the legal responsibility of the Notary for the criminal act of forgery of the Authentic Deed he made in Judge Decision Number 248/Pid.B.2022 /Notary in the Nirina Zubir case can be held accountable administratively and criminally, namely Article 264 paragraph (2) of the Criminal Code, Article 55 paragraph (1) of the Criminal Code and Article 3 of Law No. 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering and Legal consequences arising from the criminal act of forgery